Students' logical-mathematical intelligence through the problem-solving approach. (February 2020) - Azinar, J A; Munzir, S; Bahrun,
Abstract: Logical-mathematical intelligence is one of the most dominant components of multiple intelligences in mathematics learning because it can be built in all topics in mathematics. Logical-mathematical intelligence is the ability of students in terms of numbers and logic, which involves the skills to process words and numbers, to use logic and analyze problems logically, to find formulas and to do investigations scientifically. The purpose of this study is to describe the logical-mathematical abilities of high school students. A total of 25 seventh-grade students in a junior high school in Banda Aceh participated in this study, but only three of them, with high, medium, and low criteria of logical-mathematical intelligence based on the test results, were selected to observe and analyze their logical-mathematical abilities. Data were conducted from a test and interview. The instrument used in this study was a student test sheet. The results showed that only a small number of students (three out of 25) had logical-mathematical intelligence in the indicators of numeracy and problem-solving. Then, it can be concluded that the students' logical-mathematical intelligence is still low and needs to be further investigated.